Efficacy of African Union’s actions to fight terrorism in Africa. The cases of Somalia and Nigeria - Barrantes Sánchez, Johanna (2019)
This article deals with the problem of terrorism in Africa. It parts from thebackground of this phenomenon in the continent, and then it presents twocase studies, the terrorist group Al-Shabaab in Somalia and the group BokoHaram in Nigeria. The aim of this article is to analyze the efficacy of theAfrican Union in the fight against terrorism, starting from the its actions inthe two case studies, and it seeks to demonstrate the high incidence of extraregionalactors in the continent.